Robustness as performance Indicator for masonry arch bridges - Moreira, Vicente Novo (2016)
Masonry arch bridges date from past centuries, being preserved over the years due their historical importance. According to the Sustainable Bridges Project, around 40% of all European bridges are masonry arch bridges. However, some of these bridges have suffered deterioration over time and, in some cases, safety can be compromised. In order to avoid such desirable events, the concept of robustness arises. Structural robustness has gained a high interest after the collapse of the World Trade Centre. In fact, robustness can be defined as the ability of a structure to support a certain amount of damage without global collapse occurrence. A structure is considered robust when it is designed with very resistant components and presents a progressive collapse when one of these components fails. Over the last years, several methods have been proposed to quantify the robustness, namely: (1) risk-based robustness index; (2) reliability-based robustness index; (3) deterministic robustness index based on experimental data. This work aims to present the quantification of the robustness index for a masonry arch bridge in order to assess its structural condition.